A method for estimating nematode body lengths for use in the calculation of biomass via a simplified formula. (July 2019) - Zhao, Jie; Xiao, Jun; Zhang, Wei; Fu, Zhiyong; Zhang, Mingyang; Liu, Tao; Tan, Qiujin; Wang, Kelin
Abstract: Soil nematode biomass is related to a number of soil ecological processes and functions. Nematode shape is simple, i.e., they have elongate cylindrical bodies that taper towards both ends. Consequently, the weight of an individual nematode can be estimated from its greatest body diameter ( D ) and body length ( L ), using a simple formula developed by Andrássy. Because heat-killed and fixed nematodes often have non-linear, irregular shapes, however, it is easier to measure D than L . To reduce the time required to assess an individual nematode's weight, we propose a new method of calculating nematode weight with D as the single measure. Our formula was based on the recognition of a strong linear correlation between D and L . The performance of our formula was compared with Andrássy's formula for the whole nematode community and for nematode trophic groups in an area with four land use types. The nematode weights calculated with these two formulas were positively correlated, and the slopes of the regressions between the two biomass estimates were close to 1 for the whole nematode community and the five trophic groups. In addition, there was no difference in the outcome due to land use type, indicating that the proposed formula may be generally useful for assessing nematode weights in terrestrial ecosystems. We also propose to include five trophic group-specific factors in the new formula for more accurate assessments. Highlights: Nematode size varies significanlty due to the greatest body diameter and body length. The greatest body diameter is correlated linearly to body length. New formula proposed to calculate nematode weight based on greastest body diameter. The new formula is suitable for calculating nematode weight.